Twisted coadmissible equivariant D-modules on rigid analytic spaces - Mathers, R (2019)
We aim to extend the results of Ardakov and Wadsley on representations of p-adic Lie groups and sheaves of equivariant D-modules on rigid analytic spaces. Our main results are a canonical dimension estimate for coadmissible representations of a semisimple p-adic Lie group in a p-adic Banach space, and a Beilinson-Bernstein-type localisation for coadmissible equivariant Dλ -modules, where λ is a ρ-dominant ρ-regular infinitesimal central character.